The Case for "Unfair Methods of Competition" Rulemaking - Chopra, Rohit; Khan, Lina M. (The University of Chicago law review, 2020)
A key feature of antitrust today is that the law is developed entirely through adjudication. Evidence suggests that this exclusive reliance on adjudication has failed to deliver a predictable, efficient, or participatory antitrust regime. Antitrust litigation and enforcement are protracted and expensive, requiring extensive discovery and costly expert analysis. In theory, this approach facilitates nuanced and fact-specific analysis of liability and well-tailored remedies. But in practice, the exclusive reliance on case-by-case adjudication has yielded a system of enforcement that generates ambiguity, drains resources, privileges incumbents, and deprives individuals and firms of any real opportunity to participate in the process of creating substantive antitrust rules. It is difficult to quantify this harm. This Essay argues that rulemaking under § 5 of the Federal Trade Commission Act should supplement antitrust adjudication, and that this institutional shift would lower enforcement costs, reduce ambiguity, and facilitate greater democratic participation. We build on existing scholarship to debunk the view that the Federal Trade Commission (FTC) does not have competition rulemaking authority pursuant to the Administrative Procedure Act conferring Chevron deference, and trace legislative history to underscore how Congress designed the FTC to play a unique institutional role. We close by outlining an initial set of factors that should weigh in favor of rulemaking: when there is significant learning from past enforcement and when private litigation would be unlikely. Finally, we pose questions in the context of the FTC's recent hearings to prompt further discussion on where this unused tool would be most useful.